Financial shocks, job destruction shocks, and labor market fluctuations - Zanetti, F (Cambridge University Press, 2017)
This paper investigates the effect of financial shocks using a general equilibrium model that links the firm's flows of financing with labor market variables. The results show that financial shocks have sizeable effects on debt, dividend payout, and wages. Shocks to the job destruction rate are important in explaining fluctuations in unemployment. The analysis also investigates the underlying driving forces of some key comovements in the data and finds shocks to the job destructions rate important.